1, 25-OH2 vitamin D3 and AKT-inhibition increase glucocorticoid induced apoptosis in a model of T-cell acute lymphoblastic leukemia (ALL). (2018) - Pistor, Maximilian; Schrewe, Lisa; Haupeltshofer, Steffen; Miclea, Andrei; Faissner, Simon; Chan, Andrew; Hoepner, Robert
Abstract: In acute lymphoblastic leukemia (ALL), steroid resistance and hypovitaminosis D are both associated with a poor prognosis. We show that methylprednisolone, calcitriol and the AKT-inhibitor MK-2206 have a synergistic effect on the apoptosis of steroid resistant T-ALL cells. Compared to methylprednisolone monotherapy, calcitriol increases methylprednisolone induced apoptosis dose-dependently (1.37–1.92-fold; p < 0.05). Pre-incubation with calcitriol increases the apoptotic effect of MK-2206 even further (3.6-fold; p < 0.05). It also potentiates synergism between MK-2206 and methylprednisolone (vehicle control 38% vs. calcitriol 58%, p < 0.01). The combination of calcitriol and AKT inhibition should be investigated further as treatment options for steroid resistance in T-ALL.